White snow, bright snow - Tresselt, Alvin, 1916-2000.; Duvoisin, Roger, 1900-1980 (New York : Mulberry Books, 1988)
When it begins to look, feel, and smell like snow, everyone prepares for a winter blizzard.
"A Caldecott medal book"--P. [4] of cover.
"An ALA notable book"--P. [4] of cover.
Art techniques used: Acetate color separations in 4 colors made by brush and india ink.
Caldecott Medal, 1948.
Keywords: Snow -- Fiction; Snow -- Juvenile fiction; Caldecott Medal Winner